Cultural Differences in the Efficacy of Group Psychotherapy for Social Anxiety Disorder: A Meta-Analysis Comparing Asia and Western Countries - Febrianthi, Adinda Nasha Ayu; Yudiarso, Ananta (Jurnal Online Psikogenesis, 2025)
This study aims to evaluate the effectiveness of group-based psychotherapy interventions in reducing social anxiety. This meta-analysis included 12 articles involving 539 participants (323 in the intervention group and 216 in the control group). This study hypothesized that group psychotherapy is effective in reducing the symptoms of social anxiety disorder. Data analyzed included sample size (N), mean (M), and standard deviation (SD) to calculate the effect size using a random-effects model. The results showed a Hedge’s g effect size of -0.809 (95% CI -1.202 to -0.416) with moderate heterogeneity (I² = 73.84%). Moderator analysis based on country of origin revealed a difference in effect size of -1.217 (95% CI -2.109 to -0.325) with lower heterogeneity (I² = 61.28%). These findings indicate that group-based psychotherapy is significantly effective in reducing social anxiety. Furthermore, Asian countries demonstrated greater effectiveness compared to Western countries in using group psychotherapy to alleviate social anxiety symptoms. This study highlights the importance of incorporating cultural contexts into the development of group psychotherapy interventions.